Desafios em rede: estudo do percurso histórico do grupo condutor municipal da Rede de Cuidados à Pessoa com Deficiência do Município de Santos/SP - Gaspar, Naira Rodrigues [UNIFESP] (2017)
Bearing in mind the historical invisibility of people with disabilities in our society and the shortage of the supply of health services that fully meet their care needs, the Ministry of Health established, in 2012, the Health Care Network for People with Disabilities, which, as Unified Health System structural policy, aims to organize the points of attention, changing meaning to practices targeting this public. In 2013, the Municipal Department of Health in the city of Santos/SP started the work of the Municipal Conductor Group, which follow the guidelines developed by the Ministry of Health and provides for the points of attention mix to the health care of people with disabilities, developing the design of municipal care network and the contract of its points of attention. This research aimed to study the historical background of the Municipal Conductor Group in the construction of the Person Care Network with Disabilities in Santos, from March 2014 to December 2016. The choice of thematic oral history method, through narratives of the journeys of Municipal Conductor Group members, contributed to the construction of a narrative that enables the understanding of the links between the group's history, the care model proposed by the Health Care Network for People with Disabilities and the redefinition of health practices related to this population in the municipality. Aspects related to the conception of disability and personal constructs about the care representations emerged in a recurring way in the narratives, as well as the power of the GCM in strengthening health policies for this public. The results showed that people with disabilities need more accessible practices and services that address their needs.